Prognostic Factors and Features of Endometrial Cancer in Women with Metabolic Syndrome - Olha M. Serhiivna, Pavlo T. Romanovych, Kateryna K. Stepanivna (Open Journal of Physicians and Surgeons, 2025)
Endometrial cancer (EC), according to world statistics, occupies a leading position in the structure of oncogynecological morbidity and mortality from malignant neoplasms. Over the period from 1996 to 2007, the proportion of patients with identified stages I-II of the process increased (61.6%) and one-year mortality decreased to 11.5%. Patients with stages III and IV of the tumor process make up 25.4% and 11.9%, respectively. Endometrial cancer is characterized by a heterogeneous nature, which is manifested at the level of both risk factors and pathogenesis. At the same time, endocrine elements constitute an important part of the overall picture and interact with a complex of molecular-genetic and other factors, which should determine the features of the formation of risk groups and ways of preventing this disease. At present, the concept of metabolic syndrome X has been formulated, according to which obesity, mainly of the android type, arterial hypertension, dyslipidemia, and impaired glucose tolerance are links in a single chain of metabolic disorders, the leading link in which is insulin resistance and compensatory hyperinsulinemia. The frequency of metabolic syndrome in the adult population is 15-20%. Patients with metabolic syndrome are more prone to the development of a number of malignant neoplasms than in the population as a whole [14,19,22,36]. The risk of developing EC against the background of metabolic syndrome increases by 2-3 times.